The role of interactive gamification through Wordwall Apps to improve students’ engagement and literary comprehension - Najihah Abd Wahid; Farhan; Mualim Wijaya (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2025)
Background: This study explores the efficacy of interactive gamification through Wordwall Apps in enhancing literary comprehension and student engagement in educational settings. Objective: The aim is to determine whether gamification techniques with Wordwall Apps can significantly improve literary learning outcomes compared to traditional teaching methods. Method: Utilizing a quasi-experimental design, the research involved control and experimental groups from a sample of high school students, where the latter engaged in gamified learning activitie with Wordwalls. Results: The findings reveal that Wordwall gamification markedly increases student engagement and deepens literary comprehension, as evidenced by higher post-test scores in the experimental group compared to the control. Implication: These results suggest that interactive gamification not only makes learning more enjoyable but also more effective, encouraging a deeper interaction with literary content. Novelty: This not only renews the pedagogical perspective but also broadens the educational discourse by introducing dynamic variables and methods that address the cognitive needs of the modern learner.